Metoda Pengolahan Limbah Terpilah Pada Industri Penyamakan Kulit - Kendedes Y (Balai Besar Kimia dan Kemasan, 2001)
Waste water from leather tanning industries contains high pollutant of organic and inorganic matters. Fragmented method of waste water treatment management has been done in PT K, leather tanning industry, Malang. This method based on the characteristic ot the waste water from each leather tanning process with four group treatment process to reduce the COD content. By implementing this method the result shows that the COD content decreasing from 4047,68 ppm to 793,37 ppm (80,40 %); other benefit is reducing bad smell during the process.